2018
DOI: 10.1016/j.ympev.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Extreme halophilic archaea derive from two distinct methanogen Class II lineages

Abstract: Phylogenetic analyses of conserved core genes have disentangled most of the ancient relationships in Archaea. However, some groups remain debated, like the DPANN, a deep-branching super-phylum composed of nanosized archaea with reduced genomes. Among these, the Nanohaloarchaea require high-salt concentrations for growth. Their discovery in 2012 was significant because they represent, together with Halobacteria (a Class belonging to Euryarchaeota), the only two described lineages of extreme halophilic archaea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 54 publications
4
57
0
1
Order By: Relevance
“…Organismal scope or featured taxon Cunha & Giribet (2019) yes Gastropods Laumer et al (2019) yes Animals Lemer et al (2019) yes Bivalves Lozano-Fernandez et al (2019) yes Chelicerates Marlétaz et al (2019) yes Spiralia Philippe et al (2019) yes Bilateria Narayanan Kutty et al (2019) no Calyptratae Uribe et al (2019) no Gastropods Wolfe et al (2019) no Decapod crustaceans Zverkov et al (2019) no Dicyemida and Orthonectida Aouad et al (2018) yes Archaea Laumer et al (2018) yes Placozoa Otero-Bravo et al (2018) yes Pantoea Puttick et al (2018) yes Land plants Schwentner et al (2018) yes Pancrustacea Sousa et al (2018) yes Land plants Bennett & Mao (2018) no Fulgoroidea symbionts Eitel et al (2018) no Placozoa Manzano-Marín et al (2018) no Cinara strobi symbionts Feuda et al (2017) yes Animals Szabó et al (2017) yes Pseudococcidae symbionts Williams et al (2017) yes Archaea Schwentner et al (2017) no Pancrustacea Shin et al (2017) no Curculionoidea Simion et al (2017) no Animals Yoshida et al (2017) no Tardigrades Leliaert et al (2016) yes Viridiplantae Zhang et al (2016) yes Roseobacter CHAB-I-5 lineage He et al (2016) no Rhizaria Song et al (2016) no Holometabola Domman et al (2015) yes Plastids Luo (2015) yes SAR11 Petitjean et al (2015) yes Archaea Borowiec et al (2015) no Animals Derelle et al (2015) no Eukaryotes Wang & Wu (2015) no Mitochondria…”
Section: Citationmentioning
confidence: 99%
“…Organismal scope or featured taxon Cunha & Giribet (2019) yes Gastropods Laumer et al (2019) yes Animals Lemer et al (2019) yes Bivalves Lozano-Fernandez et al (2019) yes Chelicerates Marlétaz et al (2019) yes Spiralia Philippe et al (2019) yes Bilateria Narayanan Kutty et al (2019) no Calyptratae Uribe et al (2019) no Gastropods Wolfe et al (2019) no Decapod crustaceans Zverkov et al (2019) no Dicyemida and Orthonectida Aouad et al (2018) yes Archaea Laumer et al (2018) yes Placozoa Otero-Bravo et al (2018) yes Pantoea Puttick et al (2018) yes Land plants Schwentner et al (2018) yes Pancrustacea Sousa et al (2018) yes Land plants Bennett & Mao (2018) no Fulgoroidea symbionts Eitel et al (2018) no Placozoa Manzano-Marín et al (2018) no Cinara strobi symbionts Feuda et al (2017) yes Animals Szabó et al (2017) yes Pseudococcidae symbionts Williams et al (2017) yes Archaea Schwentner et al (2017) no Pancrustacea Shin et al (2017) no Curculionoidea Simion et al (2017) no Animals Yoshida et al (2017) no Tardigrades Leliaert et al (2016) yes Viridiplantae Zhang et al (2016) yes Roseobacter CHAB-I-5 lineage He et al (2016) no Rhizaria Song et al (2016) no Holometabola Domman et al (2015) yes Plastids Luo (2015) yes SAR11 Petitjean et al (2015) yes Archaea Borowiec et al (2015) no Animals Derelle et al (2015) no Eukaryotes Wang & Wu (2015) no Mitochondria…”
Section: Citationmentioning
confidence: 99%
“…In turn, these analyses suggest that conflicting results regarding the placement of certain DPANN lineages, may be due to, at least in part, to the use of a large number of markers affected by host-symbiont HGT. For instance, Nanohaloarchaeota may artificially be drawn towards the Euryarchaeota 28 when marker sets include too many proteins that were affected by symbiont-host transfers.…”
Section: Resultsmentioning
confidence: 99%
“…Ever since the discovery of the first DPANN representative - Nanoarchaeum equitans , an ectosymbiont of Ignicoccus hospitalis 15 - the phylogenetic placement of putative DPANN clades in the archaeal tree have been uncertain 26 . While various phylogenetic analyses have indicated that DPANN may comprise a monophyletic radiation in the Archaea 10,11,27 , these have been debated 8,28,29 . In particular, analyses focusing on the placement of selected DPANN lineages in isolation, such as Nanoarchaeota and Parvarchaeota, relative to other Archaea, have led to the conclusion that these represent fast-evolving Euryarchaeota 28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Haloarchaea have been shown to engage in phototrophy in microaerobic or anoxic laboratory conditions (Sumper et al, 1976;DasSarma et al, 2012;Laye et al, 2017). Additionally, a considerable amount of evidence suggests that the genes for aerobic respiration were laterally transferred to halophilic Archaea (Kennedy et al, 2001) and their ultimate origin may have been as an anaerobic chemolithoautotrophic methanogen (Nelson-Sathi et al, 2012;Aouad et al, 2018). Hence, haloarchaeal phototrophic metabolism was probably developed well before genes for aerobic respiration were acquired, possibly in Archaea inhabiting hypersaline environments (Stevenson et al, 2015).…”
Section: Appearance Of Purple Retinal Pigmentsmentioning
confidence: 99%